Study on the desulfurization performance of N-Type and P-Type semiconductor pyrolysis char composite catalyst - Lei Zhang (Journal of Environmental Science and Management, 2017)
Ordos coal pyrolysis product roasted under 750oC was used as desulfurization sorbents to investigate the effect of flue gas desulfurization performance of supported metal catalyst. There were 14 kinds of metal oxides from groups IA, IIA, VIB, VIIB, VIII, IB and IIIB chosen as active components to prepare metal oxide supported catalysts by equivalent volume impregnation method. And the mechanism of pyrolysis was studied. The similarities of desulfurization performance among the same group of metal oxides were related to the structure of their outer electrons. In addtion, the influence of transition metal oxides on the desulfurization performance was related to metal oxide semiconductor type. Finally, the influence of the VIII group oxide catalyst of iron (Fe), Cobalt (Co), Nickel (Ni) on the desulfurization performance showed the characteristics of diversity related to their d percentage (%).